Managing Diversity in History Learning Based on the Perspective of Kakawin Ramayana (History Department, Semarang State University and Historian Society of Indonesia, 2020)
This research aims to build a framework of diversity management in history learning based on the reinterpretation of diversity from the perspective of Kakawin Ramayana. The authors used a critical hermeneutic approach to interpret the texts of Kakawin Ramayana, especially in the texts of Prěthiwi and Aṣṭabrata. The text of Prěthiwi and Aṣṭabrata implicitly elucidates that diversity should be acknowledged based on the moral and ethical attributes of an individual. There are no spaces for arbitrary prejudices based on social identities, such as ethnicity, race, or even religiosity and political affiliation. The findings of the research show that the framework of diversity management in history learning can be built by creating three layers: (1) inclusive curriculum, (2) alternate narratives in learning materials and history textbooks, and (3) teacher and students’ attitude of multi-perspectivity. The history curriculum has to accommodate inclusiveness by acknowledging social and psychological diversity. Along with the inclusive curriculum, history textbooks should provide alternate narratives in the form of personal or biographical history as the third way to counter the grand narratives and present the multi-narratives in learning history. Teachers and students have to accept multi-perspectivity as the representation of diversity in history learning. The authors believe that these layers of diversity management can provide a prolific understanding of diverseness and its relativity in history learning in which diversity could not be merely observed in the societal term but also the personal parameter. Penelitian ini bertujuan untuk membangun kerangka manajemen keberagaman dalam pembelajaran sejarah berbasis reinterpretasi kebhinekaan dari perspektif Kakawin Ramayana. Penulis menggunakan pendekatan hermeneutik kritis untuk menafsirkan teks Kakawin Ramayana, terutama dalam teks Prěthiwi dan Aṣṭabrata. Teks Prěthiwi dan Aṣṭabrata secara implisit menjelaskan bahwa keberagaman harus diakui berdasarkan atribut moral dan etis seseorang. Tidak ada ruang untuk prasangka sewenang-wenang berdasarkan identitas sosial, seperti etnis, ras, atau bahkan religiusitas dan afiliasi politik. Hasil penelitian menunjukkan bahwa kerangka kerja manajemen keberagaman dalam pembelajaran sejarah dapat dibangun dengan membuat tiga lapisan: (1) kurikulum inklusif, (2) narasi alternatif dalam materi pembelajaran dan buku teks sejarah, dan (3) sikap guru dan siswa. multi-perspektif. Kurikulum sejarah harus mengakomodasi inklusivitas dengan mengakui keragaman sosial dan psikologis. Seiring dengan kurikulum inklusif, buku teks sejarah harus memberikan alternatif narasi berupa sejarah personal atau biografis sebagai cara ketiga untuk melawan narasi besar dan menyajikan multi narasi dalam pembelajaran sejarah. Guru dan siswa harus menerima multiperspektif sebagai representasi keberagaman dalam pembelajaran sejarah. Penulis percaya bahwa manajemen keanekaragaman ini dapat memberikan pemahaman yang produktif tentang keanekaragaman dan relativitasnya dalam pembelajaran sejarah di mana keanekaragaman tidak dapat hanya diamati dalam konteks masyarakat tetapi juga level pribadi.